Minimal activity of nanoparticle albumin-bound (nab) paclitaxel in relapsed or refractory lymphomas: results of a phase-I study. Issue 2 (1st February 2018) - Goyal, Sagun; Oak, Eunhye; Luo, Jingqin; Cashen, Amanda F.; Carson, Kenneth; Fehniger, Todd; DiPersio, John; Bartlett, Nancy L.; Wagner-Johnston, Nina D.
Abstract: Compared with solvent-based taxanes, nanoparticle albumin-bound (nab ® ) paclitaxel has demonstrated improved efficacy and tolerability in several solid tumor malignancies. Studies evaluating nab paclitaxel in patients with lymphoma are lacking. In this planned phase-I/phase-II study, we sought to determine the safety and efficacy of nab-paclitaxel in patients with relapsed/refractory (R/R) lymphoma. Eligible patients (R/R to ≥2 prior systemic therapies) received weekly nab-paclitaxel on days 1, 8 and 15 every 28 days. Dosing was initiated at 100 mg/m 2 with dose escalations in 25 mg/m 2 increments up to 150 mg/m 2 in a classic 3 + 3 design. Twenty heavily pretreated patients (median 5 prior regimens), including 65% with refractory disease, enrolled. The maximum dose tested was well tolerated and grade 3/4 hematologic adverse events (neutropenia 25%, thrombocytopenia 20% and anemia 15%) were modest. The overall response rate was 10% with two partial responses, leading to a decision to close the study prematurely.